Hereditary Nonpolyposis Colorectal Cancer in Association with Crohn’s Disease and Lynch Syndrome: The Importance of a Strict Endoscopic Surveillance - Gustavo Drügg Hahn; Panu Wetwittayakhlang; Waqqas Afif; Talat Bessissow; Peter L. Lakatos (Case Reports in Gastroenterology, 2022)
Crohn’s disease (CD) and Lynch syndrome (LS) are two different entities, yet both are associated with increased risk of colorectal cancer (CRC). We present the case of a young female patient in long-standing remission of her ileocolonic luminal CD, and a family history of LS on a regular short interval (every 2 years) colonoscopy surveillance. Despite normal blood tests, fecal calprotectin, and ileocolonoscopy, her last colonoscopy showed an approximately 1.3–1.5 cm polyp in the cecum and mild UC-like colitis in the ascending colon. Histology confirmed the presence of a moderately differentiated adenocarcinoma (T2N0M0) with loss of PSM2 expression at immunohistochemistry, in line with a hereditary nonpolypoid CRC associated origin. Laparoscopic subtotal colectomy with ileorectal anastomosis was offered as the treatment of choice, which revealed a 2.4 cm exophytic ulcerated lesion and pathology confirmed invasive moderately differentiated adenocarcinoma (pT2N0M0). Patient will remain on close endoscopic surveillance for the rectum. Our case highlights the importance of a strict endoscopic surveillance in patients with long-standing CD colitis, especially in patients with additional risk factors. The aim of this article was to highlight the importance of a strict endoscopic surveillance in CD in association with LS regarding a higher risk of CRC, which mandates the adaptation of the endoscopic surveillance intervals as well as the surgical approach and postoperative management/surveillance.